Nivel socio-económico familiar y su incidencia en la formación académica de los estudiantes del 5to año de EGB de la UE Emigdio Esparza Moreno, Babahoyo. 2022 - Jiménez Herrera, Álvaro Andrés (2022)
The present supporting document of the complex examination of degree prior to obtaining the title of Bachelor of Science in Education entitled "Family socio-economic level and its impact on the academic training of the students of the 5th year of EGB of the EU Emigdio Esparza Moreno, Babahoyo. 2022, maintains the objective of determining the incidence of the family socio-economic level in the academic training of the students of the 5th year of EGB through a bibliographic review and a questionnaire, of closed questions, in a qualitative and quantitative way to four teachers who teach classes. to the 5th year of EGB, which mentions that problems in the family nucleus are the first cause to change the teaching-learning environment, in a child who is susceptible to everyday situations. Within the relationship that exists between academic training and the family's socio-economic level, solutions were proposed in accordance with the requirements of society, such as emotional help from the teacher and the continuous improvement of the pedagogy to be used. It is recommended to develop a case analysis for the entire EU, in order to generate a clearer and more detailed picture of the real situation of the students who make up this institution and who can take advantage of the possible solutions in favor of improving academic performance.